Pengaruh Metode Eksperimental Pada Pemahaman Konsep, Bahan, Sifat dan Perubahan Bentuk Benda - Siti Auliasari Argita Vandho; Harun; Risky Dwi Cahya (Jurnal Penelitian Pendidikan IPA, 2024)
Students' conceptual understanding of science learning is relatively low. Another factor that causes low understanding of students' concepts is because students have not been invited to directly experiment or conduct direct experiments in science learning, especially the material on the properties of objects and various changes in the state of objects. This study aims to see the effect of the experimental method on the conceptual understanding of fourth grade elementary school students. This study is a quantitative study with a pre-experimental method. The design of this study uses The One-Group Pretest-Posttest Design. The population in this study were all fourth grades elementary school students. The sample selection used the Purposive Sampling technique. The sample used in this study was 30 fourth grade students of SDN 3 Muara Enim. The research instrument used to measure students' conceptual understanding used pretest and posttest questions. The data obtained were then analyzed using SPSS 25.0 to test normality, homogeneity, and the One Sample T-Test hypothesis test. The results of the data analysis showed that the experimental method had an effect on the understanding of fourth grade elementary school students on the material on the properties and changes in the state of objects as evidenced by the results of the hypothesis test of 0.000.